Value of intraoperative consultation with the pathologist in differentiated carcinoma thyroid and its impact on the extent of the glandular resection - Delgado, Bolívar; Yametti, Luis; bott, Fernando (Cirugía del Uruguay, 1992)
The results of a series of 163 operated nodules which were studied by intraoperative freezing is analysed. The following are emphasized: a sensitivity of 89.6%, a specificity of 95.8%, 1.8% false negatives, 3% false positives and a reduction of extension of glandular resection in 51 %.